Pengaruh Media Pembelajaran PowerPoint Interaktif terhadap Hasil Belajar Ilmu Pebgetahuan Alam (IPA) Siswa Kelas V di SDN Gunung Gatep Tahun Ajaran 2025/2026 - Bentar Purnomo Suara; Muhammad Makki; Mansur Hakim; Syarifuddin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the effect of interactive PowerPoint  learning media on the science learning outcomes of fifth-grade students. The research approach used is quantitative with a Quasi-Experimental design, specifically Nonequivalent Control Group Design. The sampling technique uses saturated sampling, where the entire population of two classes is used as a research sample with class VA (experimental) and class VB (control). The research instrument is a multiple-choice test that has passed the validity test. The data were analyzed through prerequisite tests, including the normality test (Shapiro-Wilk) and homogeneity test (Levene's Test), before continuing with hypothesis testing using the Polled Variance Test. The results showed that the sig. (2-tailed) value was 0.00 <0.05, with the average score of the experimental class   (84,36  ) higher than the control class( 65,18). With a total sample of 44 students (22 per class), the results of the statistical test showed that Ho was rejected and Ha was accepted, so it can be concluded that interactive PowerPoint  media has a significant effect on the science learning outcomes of fifth-grade students.